P+šr + Personal Name: An Expression of Genealogical Relations? - Jennes, Gwen (Zeitschrift für ägyptische Sprache und Altertumskunde, 2013)
This paper focusses on one specific naming type that is mainly attested during the Graeco-Roman Period. ‘Psen/Sen + PN names’ are based on a popular theophoric naming type, but the god’s name has been replaced by an anthroponym. First, attention is paid to the type itself. The differences between male and female names are discussed, as well as the type’s geographical spread and its chronological evolution. An overview of the most popular names is also provided. The second part pays attention to people’s motives when bestowing such a name upon their child. Did people still understand the meaning of these names? Are the personal names featuring in this type those of deified persons, or do these names actually express a genealogical relation?